PERANCANGAN SISTEM INFORMASI AKUNTANSI ENTITAS NIRLABA DALAM PENYAJIAN LAPORAN KEUANGAN BERBASIS AKUNTABILITAS MASJID - Firdaus, Dony Waluya; Yulianto, Hery Dwi (Jurnal Riset Akuntansi dan Keuangan, 2018)
The design of accounting information systems for non-profit entities to improve accountability in presenting the mosque's financial statements. Non-profit entity accounting information system using Enterprise Resources Planning (ERP) is odoo accounting. Approach to ERP methodology using ASAP (Accelerated SAP) methodology, software development stage using Software Development Life Cycle (SDLC), in design using DFD and system flowchart.Â Keywords: Accountability; Non-Profit Entity; Enterprise Resources Planning; Financial statements; Odoo Accounting; Accounting Information System Design.